PEMAHAMAN UU CIPTA KERJA DAN IMPLIKASINYA TERHADAP SUSTAINABLE DEVELOPMENT PADA DINAS LINGKUNGAN HIDUP KABUPATEN BEKASI - Rahmat Saputra; Rama Dhianty (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
This activity was carried out because the process ofratifying the Employment Copyright Act had pros and cons forenvironmental protection. The regulation uses the omnibus lawmethod which changes, revises, revokes, and abolishes 79 laws.These changes are related to Law no. 32/2009 concerning PPLHwhich is related to the abolition of the Amdal assessmentcommission, in the preparation of the Amdal which does notinvolve the community, what are the competency criteria forAmdal compilers, and so on. The location of the activity is theBekasi Regency Environmental Service. The number ofparticipants is 100 people. The model used is legal counselingrelated to the development of the job creation law and itsimplications for sustainable development at the Bekasi RegencyEnvironmental Service. The method of activity is a presentationthrough a Webinar because it is still in the PPKM condition dueto the Covid 19 pandemic. The results of this counseling canincrease the understanding of local government employees,environmentalists, initiators, and the public which have animpact in particular on the ratification of the Job Creation Actand its derivatives which resulted in changes to Law no. 32/2009concerning the Protection and Management of the Environment,and the socialization of the legal rules governing the JobCreation Law and its implementing regulations as a result of theamendment to Law no. 32/2009 on Environmental Protection andManagement.